Influence of P, S, O-Doping on g-C3N4 for hydrogel formation and photocatalysis: An experimental and theoretical study. (November 2020) - Chu, Yi-Ching; Lin, Tzu-Jen; Lin, Yan-Ru; Chiu, Wei-Lun; Nguyen, Ba-Son; Hu, Chechia
Abstract: Photocatalysis is a facile and eco-friendly approach for the removal of dyes and organic compounds, water splitting, and CO2 reduction and fixation. Herein we report the first use of P, S, O-co-doped graphitic carbon nitride (g-C3 N4 ) to produce a photocatalyst hydrogel. The hydrogels are generated by photoinitiated crosslinking of N, N-dimethylacrylamide and N, N-methylenebis(acrylamide) with modified g-C3 N4 materials and the photocatalytic activity is evaluated by monitoring the degradation of methyl blue (MB) solutions. S- or O-doping creates C‒S or C‒O bonds, respectively, by replacement N atoms, while P-doping produces P‒N bonds by substitution of C in the heptazine rings of g-C3 N4 . Based on a combination of theoretical calculations and experimental analyses, phosphorus, sulfur, and oxygen doping considerably facilitates charge separation across the heptazine rings and attracts photoexcited electrons, thus contributing to enhanced photocatalytic activity of doped g-C3 N4 . The P, S, O-co-doped g-C3 N4 hydrogel exhibited high photocatalytic activity for MB removal under simulated solar irradiation and could be easily isolated and cleaned for reuse. Thus, this study reports the formation of a state-of-the-art photocatalyst hydrogel from P, S, O-co-doped g-C3 N4 with enhanced photocatalytic activity and demonstrated reusability. Graphical abstract: Image 1